Ethnography of Multimodal Communication: An English-Mediated University Classroom Interaction Analysis - Wilder Yesid Escobar-Alméciga (Profile: Issues in Teachers' Professional Development)
This study combines multimodal interaction analysis and ethnography of communication to examine the social dynamics of the English classroom. It investigates the ways in which norms of interaction are established and enacted, how such norms shape and transform the social roles that class members assume in interactions, and the extent to which these norms and social roles are conducive to communicative action in pursuit of learning. Rather than approaching multimodality as the mere use of videos and pictures in pedagogical pursuits, this study examines how human interaction is populated by numerous semiotic resources and communicative modes (i.e., proxemics, gaze, gestures), and how meaning is formed and transformed in their interplay.